Graham Little-Piccardi-Lassueur syndrome in a male patient: a case report - Kulaklı, Sevgi; Ay, İlkay (The European Research Journal, 2020)
Graham Little-Piccardi-Lassueur syndrome is a type of lichen planopilaris characterized by the triad of patchy cicatricial alopecia of the scalp, non-cicatricial alopecia of the axilla and pubis, and follicular spinous papules on the body, scalp or both. This rare syndrome primarily affects middle-aged postmenopausal women with only three male cases being reported in literature. Herein we report a 53-year-old man who is fourth male patient diagnosed with Graham Little-Piccardi-Lassueur syndrome up to now.